2022
DOI: 10.1039/d2mh00376g
|View full text |Cite
|
Sign up to set email alerts
|

Toward high-performance organic photovoltaics: the new cooperation of sequential solution-processing and promising non-fullerene acceptors

Abstract: Organic Photovoltaics (OPVs) have long been a hot topic due to their light-weight, low-cost and flexibility. Simple blend-based OPVs have sufficient donor/acceptor (D/A) interfaces and high exciton dissociation efficiency, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…The improved performance of Alt− Sq versus BHJ using green solvents could be due to increased exciton dissociation and improved charge transport as a result of the sequentially deposited layers. 47,48 Charge Carrier Mobility. The charge transport properties of the three types of blade-coated active layers (BHJ, Sq, Alt-Sq) were probed using the space-charge-limited current (SCLC) method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved performance of Alt− Sq versus BHJ using green solvents could be due to increased exciton dissociation and improved charge transport as a result of the sequentially deposited layers. 47,48 Charge Carrier Mobility. The charge transport properties of the three types of blade-coated active layers (BHJ, Sq, Alt-Sq) were probed using the space-charge-limited current (SCLC) method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although Alt–Sq devices exhibit improved performance over the BHJ counterpart, the maximum FF only reached 0.50, which is comparatively low to the spin-coated BHJ devices fabricated using the o-DCB solvent. The improved performance of Alt–Sq versus BHJ using green solvents could be due to increased exciton dissociation and improved charge transport as a result of the sequentially deposited layers. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both J SC and V OC are vital parameters that affect the PCE of OSCs. [19][20][21][22][23][24] Compared with J SC and FF, V OC is the most predictable photovoltaic parameter of polymers when conceiving the molecular structure. For donor-acceptor (D-A) copolymers, the choice of strongly electron-withdrawing A units is the most efficient pathway for tuning the HOMO.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In subsequent studies, these afforded solution-and vacuum-processed merocyanine/fullerene BHJ organic solar cells (OSCs) with power conversion efficiencies (PCEs) up to 6.1%. [12,13] In contrast, our efforts to self-assemble perylene bisimide (PBI)-based NFAs into suitable functional light-harvesting and charge-transporting supramolecular structures for photocurrent generation in BHJ solar cells remained so far with limited success. [14,15] However, pioneering research from the groups of Nuckolls, [16] Yan, [17] and Wang [18] showed that the annulation of multiple PBIs units to either central cores or to oligomers afforded NFAs that yield significantly improved polymer-based OSCs with the best performance (11.2% PCE) currently achieved by a quite sophisticated and challenging to synthesize molecule bearing five PBIs annulated to a corannulene central unit reported by Wang and co-workers in 2021.…”
Section: Introductionmentioning
confidence: 99%